Javanese Cultural Locality as Perceived by KH. Bisri Musthofa: an Analysis of Tafsir QS. Luqman: 21 - Johan Alamsah; Masruchin Masruchin; Beko Hendro; Tamir Saad Ibrahim Hadri (QOF, 2024)
This research focuses on the Javanese locality in interpreting Surah Luqman: 21 in the book of tafsir al-Ibriz.. The objective is to determine the locality of Javanese culture that K.H. Bisri Musthofa incorporated into his interpretation. K.H Bisri Musthofa's reality in society is rich in cultural practices. The researchers then employed a qualitative method to collect data via library research, followed by content analysis to conclude that K.H. Bisri Mushtofa asserts that he dialogues the Qur'an with local culture to ensure the validity of his interpretation. He utilized Javanese pegon (modified Javanese script) for interpretation and incorporated instances of Javanese traditional practices, including sajen (offering), sowing porridge, and mitoni (the traditional ceremony to celebrate the seventh month of pregnancy). Then, he divided the culture that existed in Javanese society into two types.  First, some cultures should not be preserved, such as offering offerings and sprinkling porridge. This is because it is contrary to Islamic teachings.  Second, culture can be preserved because it is in accordance with Islamic teachings, the basic principle of which is almsgiving, for example mitoni.